A comparative study on retinal thickness of the macular region among AIDS patients with normal ocular fundus, HIV-related microvascular retinopathy patients, and cytomegalovirus retinitis patients - Xie, Lian-Yong (Medicine (Baltimore), 2019)
The present study aims to measure the retinal thickness of the macular region of AIDS patients with normal ocular fundus, HIV-related microvascular retinopathy patients and cytomegalovirus retinitis (CMVR) patients by optical coherence tomography, and generalize the characteristics of retinal thickness of these 3 groups of patients. In this retrospective case series, the study object comprised of 111 AIDS patients who received diagnosis and treatment in the Ophthalmology Department of Beijing Youan Hospital. There are 33 patients in the AIDS normal ocular fundus group, 47 patients in the HIV-related microvascular retinopathy group, and 31 patients in the CMVR group. The retinal thickness of the macular region of these above patients was measured. The main indicators were retinal thickness of 9 macular partitions, best corrected visual acuity, CD4+ T lymphocyte count, and the start of highly active antiretroviral therapy. In the CMVR group, except for the nasal-outer and temporal-outer sectors, the thickness of the affected eye of the rest of the regions was greater than that of healthy eye (P < .05). Furthermore, there was a difference in thickness of the superior-outer and inferior-outer sectors between the AIDS normal ocular fundus group and HIV-related microvascular retinopathy group. The difference in thickness of the superior-inner sector between patients in the AIDS normal ocular fundus group and CMVR group was not statistically significant, while the difference in thickness of the rest of the regions was statistically significant. The difference in thickness of various regions between patients in the HIV-related microvascular retinopathy group and CMVR group was statistically significant. The retinal thickness of patients in the CMVR group generally increased, the retinal thickness of superior-outer and inferior-outer sections of patients in the HIV-related microvascular retinopathy group increased, when compared to the AIDS normal ocular fundus group. These optical coherence tomography (OCT) examination results present its own characteristics in different eye diseases in AIDS patients, and different stages of eye disease.